Contesting the Discourse of Moderation: An Analysis of the MUI and Ministry of Religious Affairs’ Arguments on Interfaith Greetings - Rifqi Favian; Hanafi Arsyad (Ushuluna: Jurnal Ilmu Ushuluddin, 2025)
We will examine the differences of opinion regarding interfaith greetings between the (MoRA) Ministry of Religious Affairs and the Indonesian Ulema Council (MUI). Therefore, we discuss this debate and relate it to the discourse of moderation. We will conduct a critical discourse analysis using Norman Fairclough's theory. We will code data from the websites of both institutions and news media to investigate the social and cultural background, as well as the three dimensions of discourse: text, discursive practice, and social practice. Finally, we will examine the process of discourse production and consumption. The results show that the MUI produces this discourse based on its ideological heritage, which tends to securitize theological views that are more liberal. However, in the fatwa issued in 2024, the MUI tends to limit itself to “respecting differences” alone. This differs from the Ministry of Religion, which is more inclined to embrace religious pluralism.